Implementasi Kebijakan Pembentukan Tim Penyusunan Rencana Strategis Badan Kesatuan Bangsa dan Politik Kabupaten Ogan Komering Ilir - Herlidiwiyanti, Herlidiwiyanti; Novaria, Eva; Berlian, Ong (@-Publik: Jurnal Administrasi Publik, 2024)
This study aims to evaluate the implementation of the policy regarding the formation of the Strategic Plan (Renstra) drafting team at the National Unity and Political Agency (Kesbangpol) of Ogan Komering Ilir Regency. This policy is implemented to enhance the efficiency of planning and strategic decision-making to achieve organizational goals. Several challenges faced include suboptimal performance target achievement, influenced by factors such as limitations in planning and financing, suboptimal execution of work plans, and insufficient supporting facilities. This research uses a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observation, and documentation, then analyzed using Edward III's policy implementation model, which includes aspects of communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the policy has been well implemented, although there are some obstacles, such as the lack of human resources with specific expertise in drafting the Renstra. Communication aspects are running effectively, but there is still a need for improvement in disseminating the policy to all relevant parties. Although the available resources are adequate, enhancing quality through training and capacity development is still necessary. The disposition or attitude of the policy implementers is generally positive and supportive, but motivation and incentives are still required. The existing bureaucratic structure is fairly good, but more intensive coordination between work units is needed to ensure smoother policy implementation. Overall, this study concludes that the implementation of the policy for forming the Renstra drafting team at the Kesbangpol Agency of Ogan Komering Ilir Regency has yielded positive results, although there is still room for improvement, particularly in enhancing human resource capacity and inter-unit coordination.